Multidecadal Modulation of the ENSO Teleconnection to Precipitation and Tree Growth Over Subtropical North America. Issue 5 (27th May 2019) - Torbenson, M. C. A.; Stahle, D. W.; Howard, I. M.; Burnette, D. J.; Villanueva‐Díaz, J.; Cook, E. R.; Griffin, D.
Abstract: The teleconnection of the El Niño/Southern Oscillation (ENSO) to instrumental precipitation and temperature during the cool season over North America is strongest and most temporally stable in the TexMex sector of northern Mexico and the borderlands of southwestern United States. The ENSO impact on North American hydroclimate expands and contracts out of this region on multidecadal timescales, possibly associated with the positive and negative phases of the Atlantic Multidecadal Oscillation. A subset of tree‐ring chronologies from the TexMex sector also has the strongest and most stable ENSO signal detected in the North American network, similar to the strong ENSO signal measured in instrumental climate data from the same region. This subset of chronologies is used to reconstruct the multivariate ENSO index (MEI) as a measure of ENSO impact on North American hydroclimate during the instrumental and preinstrumental eras. The reconstruction exhibits improved fidelity in the frequency domain and better registration of spatial changes in ENSO signal over North America when compared to an MEI reconstruction based on all ENSO‐correlated tree‐ring chronologies irrespective of temporal stability of correlation. When correlated with gridded instrumental and tree‐ring reconstructed Palmer drought indices across North America, the stable MEI estimate reproduces the changes in spatial impact of ENSO signal measured with instrumental data, and it reveals similar multidecadal changes in prehistory, potentially linked to the Atlantic Multidecadal Oscillation. The Great Plains drought of the 1850s and 1860s may have been an example of this Pacific‐Atlantic configuration. Key Points: The ENSO teleconnection to North American hydroclimate varies in magnitude and spatial impact on multidecadal timescales The strongest and most stable ENSO influence is observed in the TexMex sector of northern Mexico and the borderlands of southwestern United States Tree rings reproduce these temporal and spatial changes and suggest that the changes may arise in part from North Atlantic SST variations